Effects of sacha inchi (Plukenetia volubilis) oil on the fatty acid profile, total polyphenols, antioxidant activity and sensory acceptability of dark chocolate granola bar - Ishak, I.; Ping, T.Y.; Khaironi, J.; Bakar, A.M.A.; Ahmad, F.; Ghani, M.A. (Rynnye Lyan Resources, 2024)
Sacha inchi (Plukenetia volubilis) oil is rich in polyunsaturated fatty acids (PUFAs) and antioxidants, providing essential health benefits to humans. Dark chocolate granola bar formulations enriched with sacha inchi oil were developed. In this study, sacha inchi oil (SIO) was added to a dark chocolate granola bar (DCGB) to replace butter at different percentages (0-10%). Four DCGB formulations were developed as follows: 0SIODCGB without sacha inchi oil (0%), which was used as a control sample, 2.5SIODCGB enriched with 2.5% SIO, 5SIODCGB enriched with 5% SIO, and 10SIODCGB enriched with 10% SIO. Next, the effect of SIO on the fatty acid profile, total polyphenols, antioxidant activity and sensory evaluation of DCGB were determined. The result showed that 10SIODCGB had the highest (p<0.05) amount of PUFAs (28.14%) compared to 0SIODCGB (9.54%), 2.5SIODCGB (15.13%) and 5SIODCGB (25.32%). This study also showed that the total polyphenols and antioxidant activity of DCGB enriched with SIO formulations (2.5SIODCGB, 5SIODCGB and 10SIODCGB) were significantly higher (p<0.05) than the 0SIODCGB. Regarding correlation, TPC and ferric reducing antioxidant power (FRAP) of the DCGB enriched with SIO were strongly related (r = 0.972). Meanwhile, the scores for sensory attributes of all DGCB formulations were similar (p>0.05). Therefore, the enrichment of sacha inchi oil increased the polyunsaturated fatty acids, polyphenols and antioxidant activity in the formulated dark chocolate granola bar with well-accepted by consumers.